Cooperation between the family and nurse educators - activities and satisfaction - Vasiljevic Blagojevic, Milica R.; Obradovic, Jasmina; Jovcic, Ljiljana; Rankovic, Dragica (Education and Research in Health Sciences, 2024)
Introduction: Due to the weakened educational function of the modern family, one of the basic functions of preschool institutions is to supplement family education. Considering the importance of the partnership cooperation between educators and parents with the goal of the positive, spontaneous development of the child, in this paper we research ways of realizing cooperation, as well as the satisfaction of parents and educators with their mutual cooperation. Objective: To examine the cooperation between preschool institutions and families and to determine to what extent parents and educators are satisfied with mutual cooperation. Respondents and methods: The study consists of 30 nurse educators employed at the Preschool "Vračar" in Belgrade and 30 randomly selected parents whose children attend the same preschool. For the purposes of this research, two questionnaires were formulated, for parents and for educators, in order to find out their views. Results: The results of the research show that educators estimate the greater interest of mothers in this cooperation compared to fathers, which takes place through several significant forms - individual conversation, PTA meetings, workshops. Individual conversation stands out as the most effective and most frequent form of cooperation. Furthermore, the results show that the percentage of parents’ attendance at the group form of cooperation (PTA meetings and workshops) is satisfactory and that parents and educators are satisfied with mutual cooperation. Conclusion: Based on the analyzed theoretical material and our research, we can conclude that the cooperation between families and nurse educators is satisfactory and that the best form of cooperation is individual discussion as well as PTA meetings. Improving communication skills of the nurse educators, as well as the permanent raising awareness of parents about the importance of active and continuous cooperation with preschool institutions, are key factors for the improvement of the researched process.